An Uncertain Random Programming Model for Project Scheduling Problem. Issue 1 (18th October 2014) - Ke, Hua; Liu, Huimin; Tian, Guangdong; Yang, Lixing; Li, Xiang; Ralescu, Dan A.
<x xml:space="preserve">Abstract</x> Project scheduling problem (PSP) is to determine the resource allocation schedule for the trade‐off between the project cost and the completion time. In this paper, PSP in the environment with uncertainty and randomness simultaneously is considered. In detail, the concepts of uncertain variable and uncertain random variable are introduced. Based on some concepts and theorems of chance theory, an uncertain random project scheduling model is built. For some special case, the proposed uncertain random programming model is transformed to a crisp mathematical programming model. Besides, uncertain random simulation techniques and genetic algorithm are integrated into a hybrid intelligent algorithm for searching the quasi‐optimal schedule.